FOOD LOSS AND WASTE WORLDWIDE: AN ANALYSIS OF THEORIES, ACTIONS AND GOVERNANCE - Vaz, Elisângela Domingues; Pigatto, Giuliana Aparecida Santini; Melo, Luana Fernandes (Revista Econômica do Nordeste, 2026)
Enhancing our understanding of food loss and waste (FLW) worldwide and contribute to the development of more sustainable agrifood systems is the focus of this article. For this, we analysed theories related to the theme, governance relationships in agrifood systems, and actions performed by actors of the supply network of foods, inputs, and/or materials, actors of the processing sector, and buyers. We performed a quantitative systematic literature review to map the available literature on FLW. The quantitative bibliometric tool Bibliometrix of R software was used. About findings, the main approaches included life cycle analysis for the assessment of environmental impacts, assessment of supply chain and stakeholder actions, weight estimates of food losses, discussions on circular economy, and analysis of sociotechnical transitions. The articles that addressed governance showed the need for stakeholders to contribute to the development of packaging solutions with an improved environmental profile. The originality of the study lies in its approach to the theme and the adoption of little-explored perspectives, such as theories discussing FLW and governance practices in supply chains. The study incorporates several disciplines, adopting a multidisciplinary approach. Thus, it was possible to identify significant gaps in the existing literature and suggestions for future research.